LEVEL OF KNOWLEDGE ABOUT STORAGE AND DISPOSAL OF MEDICINE AT HOME IN THE COMMUNITY OF BANJARBARU CITY, SOUTH KALIMANTAN - Okta Muthia Sari; Khoerul Anwar; Indah Pebriani Putri (Cendekia Journal of Pharmacy, 2021)
In Indonesia, the percentage of household-scale drug storage is quite large. People keep drugs for self-medication. Drugs should not be stored carelessly because it will affect the stability of the drug. In addition, the improper disposal of drugs still occurs in the community. Improper disposal of drugs can harm the environment. It is important for the public to have the correct knowledge regarding drugs in order to avoid the adverse health effects of themselves and the environment. The purpose of this study was to describe the level of knowledge of the people of Banjarbaru City about the storage and disposal of drugs at home. This research is descriptive analytic cross sectional approach with sampling technique using quota sampling. The population of this research is the entire community of Banjarbaru City, South Kalimantan. The sample size used in this study based on the Lemeshow sample calculation formula was 247 respondents. The data was taken with a validated questionnaire. The data obtained were analyzed using percentages. A total of 247 respondents met the inclusion criteria. The results showed that the majority of them were 38-47 years old, had high school and college education and worked as housewives. The level of knowledge of the people of Banjarbaru City about storing medicines at home is 39.2% less knowledge, 44.5% sufficient knowledge and 16.1% good knowledge. The level of knowledge of the people of Banjarbaru City about disposing of drugs at home is 52.6% with poor knowledge, 40.5% sufficient knowledge and 6.8% good knowledge. The knowledge of the people of Banjarbaru City about storing drugs at home is included in the sufficient level (44.5%). While the knowledge of the people of Banjarbaru City about the disposal of drugs at home is included in the level of less (52.6%).